IMPLEMENTASI GAYA DAN TEMA KONTEKSTUAL DALAM PERANCANGAN INTERIOR ERA PASCA MODERN - Aghastya Wiyoso (Universitas Trisakti, 2007)
AbstractDesign is still growing relatively as a new discipline. Now Design has already left its old paradigm, as an ornament embellishment of the product or space, to gain a new responsibility to solve advanced and complex needs of humankind behind a designed object. This change, also in the field of inten or design, acted its design process which must combine both aesthetical and rational ability. Design concept, included a theme in it, is one important step of the design process and play a role as a problem solving anticipation that can direct the whole design process to the right goal or criteria which already stated in early phase. Styles must response physically the theme establls